Transcriptional networks of transient cell states during human prefrontal cortex development - Singh, Aditi; Tiwari, Vijay K. (Frontiers in Molecular Neuroscience, 2023)
The human brain is divided into various anatomical regions that control and coordinate unique functions. The prefrontal cortex (PFC) is a large brain region that comprises a range of neuronal and non-neuronal cell types, sharing extensive interconnections with subcortical areas and plays a critical role in cognition and memory. A timely appearance of distinct cell types through embryonic development is crucial for an anatomically perfect and functional brain. Direct tracing of cell fate development in the human brain is not possible but single-cell transcriptome sequencing (scRNA-seq) datasets provide the opportunity to dissect cellular heterogeneity and its molecular regulators. Here, using scRNA-seq data of human PFC from fetal stages, we elucidate distinct transient cell states during PFC development and their underlying gene regulatory circuitry. We further reveal that distinct intermediate cell states consist of specific gene regulatory modules essential to reach terminal fate using discrete developmental paths. Moreover, using in-silico gene knock-out and over-expression analysis, we validate crucial gene regulatory components during the lineage specification of Oligodendrocyte Progenitor Cells. Our study illustrates unique intermediate states and specific gene interaction networks that warrant further investigation for their functional contribution to typical brain development and how this knowledge can be harvested for therapeutic intervention in challenging neurodevelopmental disorders.